Menjamurnya Pengaruh K-Pop di Kancah International dan Merk Global - Dinda Martalia; Gesy Lutfiah RO; Sefia Elvara Maharani (Jurnal Sosial-Politika, 2021)
K-Pop itself is a design that has been very carefully prepared to provide a new breakthrough in the field of entertainment media among the world community. With the proliferation of K-Pop among the public, this article uses conceptual results obtained from various sources available on the internet, and on all social media platforms. Currently K-Pop culture has entered international culture, even affecting the audience. The rise of K-Pop is one of the right strategies when the Korean government is intensively promoting Korean culture to the international scene. The outbreak of this k-pop fever is a step forward for the Korean state to prosper its country and we as culture connoisseurs should not swallow the culture that enters our own country raw. Keywords: Korean fever in popular culture, imitation of K-pop culture, the influence of